2007
DOI: 10.1097/inf.0b013e318124aa5c
|View full text |Cite
|
Sign up to set email alerts
|

No Decrease in Clindamycin Susceptibility Despite Increased Use of Clindamycin for Pediatric Community-Associated Methicillin-Resistant Staphylococcus Aureus Skin Infections

Abstract: A previous study at our institution revealed 98% of methicillin-resistant Staphylococcus aureus (MRSA) isolates were susceptible to clindamycin; however, beta-lactams were then the predominant empiric treatment. This follow-up chart review study examined subsequent staphylococcal skin and soft tissue infection treatment and susceptibility patterns over a 2-year period. Of 296 S. aureus skin and soft tissue infections, 73% were MRSA, of which 87% were community-associated-MRSA; MRSA infections peaked in warm su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…First, the community prevalence of MRSA colonization in children is increasing nationwide and in Baltimore ( 30 32 ), largely the result of spread of CA-MRSA strains. Second, children generally have less exposure to healthcare settings where they would be exposed to traditional HA-MRSA strains.…”
Section: Discussionmentioning
confidence: 99%
“…First, the community prevalence of MRSA colonization in children is increasing nationwide and in Baltimore ( 30 32 ), largely the result of spread of CA-MRSA strains. Second, children generally have less exposure to healthcare settings where they would be exposed to traditional HA-MRSA strains.…”
Section: Discussionmentioning
confidence: 99%
“…Clindamycin remains a mainstay of therapy for uncomplicated CA-MRSA SSTIs in much of the United States, although some researchers have suggested that resistance may be increasing among CA-MRSA strains (235,361 (874). A group from Baylor University in 2000 to 2002 found in an uncontrolled study that clindamycin was effective for invasive community-onset MRSA infections of children (585).…”
Section: Treatment Of Ca-mrsa Infections Uncomplicated Sstismentioning
confidence: 99%
“…9,10,16,[20][21][22][23][24] we observed exacerbation of lesion in summer. We report contact with soil, cow dung, intake of animal protein, excess of alcohol, excessive sweating as the precipitating factors, in line with earlier reports.…”
Section: Therapeutic Outcomementioning
confidence: 90%